"Head-to-head" double-hamburger-like structure of di-ruthenated d(GpG) adducts of mono-functional Ru–arene anticancer complexes. Issue 46 (10th November 2016) - Liu, Hong-Ke; Kostrhunova, Hana; Habtemariam, Abraha; Kong, Yaqiong; Deeth, Robert J.; Brabec, Viktor; Sadler, Peter J.
Abstract : Unusual "head-to-head" structure of a diruthenated d(GpG) adduct involving direct binding of two chelated Ru arene units to N7 of G together with additional hydrophobic arene–guanine and arene–arene interactions. Abstract : Guanine bases in DNA are targets for some Ru–arene anticancer complexes. We have investigated the structure of the novel di-ruthenated d(GpG) adduct Ru2 -GpG (where Ru = (η 6 -biphenyl)-Ru(en) 2+ (1′ )) in aqueous solution. 2D NMR results indicate that there are two conformers, supported by modeling studies. The major conformerI is a novel double-hamburger-like structure with a "head-to-head" (HH) base arrangement involving hydrophobic interactions between neighboring arene rings, the first example of a HH d(GpG) adduct constructed by weak interactions. Hence there are significant differences compared to Pt-d(GpG) adducts formed by cisplatin. There is no obviously rigid bending for the major conformerI . The minor conformerII of Ru2 -GpG has a back-to-back structure, with two ruthenated guanine bases flipped away from each other. 19-23 base-pair oligodeoxyribonucleotides containing central TGGT sequences di-ruthenated by1 show no directional bending, only slightly distorted di-ruthenated duplexes, consistent with the NMR data for conformerI . The structural differences and similarities of d(GpG) residues which are di-ruthenated or cross-linked by platination are discussed in the context of the biological activity of these metal complexes.